(untitled) (Journal of Forensic Medicine & Toxicology, 2019)
Detention is the process when a state lawfully holds a person by removing his or her freedom of liberty at that time. This can be done either in police or judicial custody for variable period of time due to pending investigation/ prosecution or to protect a person/society or property. As the freedom of liberty of the individual has been taken away by the state, medical care of the detainee is the sole responsibility of the state. On the one hand, detainee with Hep-C, diabetes, high cholesterol, high BP, multiple sclerosis, drug dependence, chronic alcoholism, chronic renal failure etc. can invite medical emergencies within hours or days of detention. On the other hand, rich and powerful/ politician/ hard core criminal when detained can feign medical emergencies for various reasons. Lack of health screening of individual by forensic physician before or after detention, lack of proper guidelines from the state or court of law and lack of proper infrastructure and facilities at detention centers thus pose serious challenge for the detaining authority. If death of such detainee occurs on any medical ground, it can raise several medico-legal issues. The present paper is an attempt to highlight those issues for better management of such detainees in Indian context.